1970
DOI: 10.3329/bjar.v33i3.1606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage containers and time on seed quality of wheat

Abstract: A study was undertaken to determine the prevalence of black point and percentages of germination, moisture content and different fungi associated with wheat seeds during storage in different types of container. Seeds of a widely cultivated variety Kanchan were stored in five types of containers viz., 'dole'(bamboo made), earthen pitcher, tin container, polyethylene bag and refrigerator (10 0 C) for ten months at room temperature. Samples were taken at monthly interval beginning from the month of April (prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 2 publications
2
25
0
5
Order By: Relevance
“…Conversely, increasing storage period from June to November significantly decreased germination percent from (91.20 to 65.41%), root and shoot length by (19.50 and 30.39%), respectively, and shoot dry weight (42.31%). Similar results were reported by Paders et al (1997) and Malaker et al (2008) who reported decreasing of seed germination from 95% to about 75% at the end of ten months of storage.…”
Section: Results Presented Insupporting
confidence: 91%
“…Conversely, increasing storage period from June to November significantly decreased germination percent from (91.20 to 65.41%), root and shoot length by (19.50 and 30.39%), respectively, and shoot dry weight (42.31%). Similar results were reported by Paders et al (1997) and Malaker et al (2008) who reported decreasing of seed germination from 95% to about 75% at the end of ten months of storage.…”
Section: Results Presented Insupporting
confidence: 91%
“…A temperatura e a umidade relativa são determinantes no processo de perda de viabilidade de sementes durante o armazenamento e alterações na qualidade do produto e, em contrapartida, dos subprodutos (Kong et al, 2008;Malaker et al, 2008).…”
unclassified
“…Aflatoxin contamination can occur at pre-and post-harvest stages (Waliyar et al, 2005). During storage, peanuts are prone to various types of deterioration some of which are attributed to growth of storage fungi which cause decrease of germination ability, loss in kernel weight, discoloration of kernels, heating and mustiness, chemical and nutritional changes, and mycotoxin contamination (Malaker, Mian, Bhuiyah, Akanda, & Reza, 2008).…”
mentioning
confidence: 99%